Value perception : managing and measuring value from the project and product management perspective - Kosovrasti, Ergys (2024)
The master thesis explores the notion of value while focusing on how value is perceived, managed, and measured throughout the project and product lifecycle. The research continues by analyzing the context of startups and small companies regarding value management practices, with the aim of creating a set of supportive guidelines. Interviews and a workshop session with participants from a SaaS startup company were conducted to gather and incorporate real-world perspectives into the research. The research utilizes methodologies such as a Systematic Literature Review and an adaptation of the Design Science Research Methodology to achieve its objectives, resulting in the creation of an artifact. The artifact serves as a starting point for creating a comprehensive guide aimed at value management practices in startups and small companies and remains available in a public GitHub repository, enabling continuous updates to reflect the current state of best practices and emerging trends.